2005
DOI: 10.1007/s10750-004-1638-z
|View full text |Cite
|
Sign up to set email alerts
|

Haematological parameters in a neotropical fish, Corydoras paleatus (Jenyns, 1842) (Pisces, Callichthyidae), captured from pristine and polluted water

Abstract: We report normal ranges of haematological indices in healthy Corydoras paleatus from an unpolluted area. Haematological parameters studied include: erythrocyte counts (Er), haematocrit (Ht), haemoglobin concentration (Hb), mean cell volume (MCV), mean cell haemoglobin (MCH) and mean cell haemoglobin concentration (MCHC). Normal red blood parameters did not change according to maturation stages, sex or seasons. Then, we compared them with those coming from fish captured in a site polluted by sewage. Fish expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 20 publications
2
38
0
1
Order By: Relevance
“…The haematological response is non-specific towards chemical stressors; however, it can indicate that fish are exposed to environmental stress (Cazenave et al 2005). Changes in red blood cell profile are probably an adaptive response to the impairment of gas exchange in copper-exposed gills and increased energetic demands on the fish (Witeska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The haematological response is non-specific towards chemical stressors; however, it can indicate that fish are exposed to environmental stress (Cazenave et al 2005). Changes in red blood cell profile are probably an adaptive response to the impairment of gas exchange in copper-exposed gills and increased energetic demands on the fish (Witeska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These parameters provide information not only about the health status of fish and the water quality in which they live, but also help to foresee, at some level, the susceptibility of organisms to changes in environmental conditions (PERCIN et al, 2010;AYOOLA et al, 2011). The physiological and metabolic response of fish to environmental changes can be examined using hematological and biochemical parameters, because blood constituents respond rapidly to any factor that affects homeostasis, including the influences of the habitat (LOHNER et al, 2001, CAZENAVE et al, 2005ELAHEE and BHAGWANT, 2007). Rapid temperature changes have the potential to dramatically affect physiological processes in aquatic organisms and, due to their limited mobility, fish in their early life stages are particularly vulnerable to ambient temperature fluctuations (COULTER et al, 2015).…”
mentioning
confidence: 99%
“…Therefore, low Hct levels in kutum in spring could be explained by their upriver migration during the spawning period that then results in the dilution of plasma content. Previous studies suggested that Hb values are the best blood indicators of environmental changes (Saint-Paul 1984;Cazenave et al 2005). Hence, low Hb values could reflect high levels of dissolved oxygen in the river that kutum move into during spring.…”
Section: Discussionmentioning
confidence: 99%